Combined effects of Limonene and Ivermectin on P-glycoprotein-9 gene expression of lambs Infected with Haemonchus contortus - Katiki, L. M.; Giglioti, R.; Ferreira, J. F.S.; Pacheco, P. A.; Barbosa, H. Z.; Rodrigues, L.; Veríssimo, C. J.; Braga, P. A.C.; Amarante, A. F.T. [UNESP]; Louvandini, H. (Elsevier, 2023)
Although ivermectin (IVM) has a wide spectrum and long half-life, its frequent use as an anthelmintic for the last 42 years led to its worldwide tolerance by Haemonchus contortus. We evaluated the combination of limonene (LIM), a P-glycoprotein (Pgp) modulator, with IVM in lambs infected with a multidrug-resistant H. contortus. Twenty-four male Dorper lambs were artificially infected with two doses (seven days apart) of 8000 infective larvae of a multidrug-resistant isolate of H. contortus. The infection was patent 25 days later. Fifteen days before treatment with IVM (DAY –15), animals were divided into 4 groups: Infected-untreated control (CTL), IVM, LIM, and LIM+IVM. From DAY –15 to DAY + 14, groups LIM and LIM+IVM received 200 mg/kg of body weight/day of LIM via oral. On DAY 0, a single dose of IVM at 200 µg/kg of body weight was administered orally to groups IVM and LIM+IVM. On DAY + 7 and DAY + 14, fecal egg counts (FEC) were performed and on DAY + 14 animals were euthanized for total worm count (TWC), worm length, fecundity of females, and Pgp-9 gene expression. On DAY + 7, group LIM+IVM had 96.29% efficacy based on Fecal Egg Count Reduction TEST (FECRT) and a highly significant reduction in FEC (P = 0.0005) when compared to CTL. On DAY + 14, the efficacy of LIM+IVM was 82.87% on FECRT, although no differences were found among groups for FEC, TWC, worm length, or Pgp-9 gene expression. Female worms from the CTL group had higher egg counts in their uterus when compared to LIM. No differences were found for hematological or biochemical parameters, body weight, or weight gain among groups. Thus, LIM given daily at 200 mg/kg was safe for animals and, when combined with IVM, decreased egg shedding and could reduce pasture contamination, although it was unable to kill multidrug-resistant H. contortus.
Keywords: Anthelmintic; Citrus sinensis; Essential oil; Natural product; Orange oil; Pgp